Perhitungan efesiensi absorber pada proses ClO2 integrated chlorine dioxide pada unit plant CM2 - Annisa, Dwi; Yusri, Muhammad; Rawadi, MHD. Raihan; Erwanto, Agus; Andika, Onil (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This study focuses on 1) Calculating the efficiency of the absorber in the Chemical making-2 Unit (CM11); 2) Finding out the factors affecting the efficiency of the absorber in Chemical making-2 (CM11). The adsorption study used a batch system. Based on observations that have been made regarding the Absorber Efficiency in the Chemical Making-2 Unit (CM 11) in the ClO2 processing at PT Indah Kiat pulp & paper Tbk. Perawang, it can be concluded that: 1) Absorption is a separation process by contacting a mixture of gas with an absorption liquid which aims to remove one of the gas components. Which here uses chilled water to absorb ClO2, the absorber used is a tray type. 2) The Absorber Efficiency obtained is 99.5%. 3) What affects the performance of the absorber in CM-11 is the placement of the Tray used and the age of the equipment used which affects the concentration of the product obtained. The concentration obtained is 9.5 gpl, this figure is categorized as meeting the standard because the ClO2 standard used by PT. IKPP Tbk. The clairvoyant is in the range of 9.5-10 gpl.